The effectiveness of compassion-based therapy on guilt and attitudes toward love in women with complex childhood trauma - Mousavi, Seyedeh Mahsa; Aghajani, Mohammad; Asgari Ghalebin, Seyedeh Sahar (Psychology of Woman Journal, 2022)
This research aims to determine the effectiveness of compassion-based therapy on feelings of guilt and attitude toward love in women with complex childhood traumas. This research was quasi-experimental in terms of the method with a pre-test-post-test design with a control group. This study's statistical population was women referred to three specialized psychology clinics in 2021-2022 in Tehran. After screening with Shame and Guilt State Scale (SSGS) and Love Attitude Scale (LAS), 30 women who obtained the desired score were selected and randomly divided into two groups of 15 people, experimental and control. The experimental group was subjected to therapeutic intervention based on compassion in the form of 8 sessions of 90 minutes once a week. The control group was placed on the waiting list for testing so that if this intervention was effective, it would also be done on them. The data obtained from the pre-test and post-test were analyzed through covariance analysis. The data from the research showed that the treatment based on compassion resulted in the reduction of guilt (F=27.13, P=0.002); improvement in attitude towards love by increasing romantic love (F=19.76, P=0.001); reduction of romantic love (F=78/12, P=0/01); increase in friendly love (F=89/92, P=0/001); increase in realistic love (F=59.91, P=0.001); reduction of extreme love (F=12.22, P=0.01); Increase in precious love (F=159.93 P=0.001). Therefore, compassion-based therapy reduces guilt and improves attitudes toward love in women with complex childhood trauma experiences.